Field evidence of flocculated sediments on a coastal algal reef - Zhi-Cheng Huang; Tian-Jian Hsu; Trung Nguyen Ly (Communications Earth & Environment)
Abstract Flocculation of sediments is crucial for morphodynamics, biogeochemical cycles, and ecological processes in aquatic environments. Here we present field evidence that bio-cohesion primarily drives the flocculation of suspended sediments on a coastal algal reef. Results from concurrent measurements of sediment mass and volume concentrations, along with Reynolds stress, reveal unexpected trends, and the data deviate from the classic Rouse formula when non-cohesive sediment is assumed. Direct estimates of particle effective density show a dependence on mean particle diameter, with a fractal dimension of 2.18. The reduced effective density (or settling velocity) and low fractal dimension are typical of flocs containing lower-density saltwater and organic materials. Additionally, organic content negatively correlates with effective density and positively correlates with the mean particle diameter, confirming that bio-cohesion drives the observed flocculation. These results provide quantitative evidence that organic matter promotes macrofloc formation and floc size growth in a reef environment.